2021
DOI: 10.48077/scihor.24(4).2021.9-16
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Features of Limphoid Tissue of the Stomach in Some Wild Bird Species

Abstract: The article presents the results of histological studies of topography, microstructure and functional features of the stomach lymphoid tissue in birds. The research was carried out on 12 species of wild birds belonging to 6 orders. Classical methods of histological specimens staining with hematoxylin and eosin, according to Weigert, Van Gieson, and argentum nitrate impregnation according to Kelemen were used when performing the work. It has been confirmed that the birds' stomach has glandular (proventriculus),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Myofibrils consisted of myofilaments and had characteristic alternating dark and light stripes. As noted in the literature (Khomych et al, 2013), since the light and dark stripes are located at the same level, the muscle fibre looks striated.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Myofibrils consisted of myofilaments and had characteristic alternating dark and light stripes. As noted in the literature (Khomych et al, 2013), since the light and dark stripes are located at the same level, the muscle fibre looks striated.…”
Section: Resultsmentioning
confidence: 54%
“…The muscle tissue of squid was white, while mussels were white and pink in colour with different markings. It was formed by smooth muscle cells that had a microscopic structure similar to the smooth muscle tissue cells of aquatic mammals (Khomych et al, 2013). These are fusiform cells with a single, centrally located oval-shaped nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some authors (Kharchenko, 2004;Khomych et al, 2020), lymphocytes in the composition of gland secretions migrate into the esophageal lumen and are involved in the formation of protective mechanisms of the immune system of the digestive organs. The lymphoid nodules in the lamina propria of the esophageal mucosa in the blackbird were not detected.…”
Section: Micromorphology Of the Esophagusmentioning
confidence: 99%
“…There are isolated clusters of lymphoid cells between them, but the lymphoid nodules are not detected (Figure 3b). Some authors report that single lymphoid nodules can be observed in the mucosa of this part of the stomach in waterfowl (Khomych et al, 2021). Between the lamina propria of the mucosa and muscularis, dense fibrous connective tissue, in which fibrocytes are visible, forms a poorly developed submucosa.…”
Section: Micromorphology Of the Stomachmentioning
confidence: 99%